2003
DOI: 10.1159/000074650
|View full text |Cite
|
Sign up to set email alerts
|

Seprase, a Membrane-Type Serine Protease, Has Different Expression Patterns in Intestinal- and Diffuse-Type Gastric Cancer

Abstract: Objective: Seprase is an integral membrane serine proteinase with gelatinase activity that may be involved in cancer invasion and metastasis. However, the pathophysiologic significance of its expression in gastric cancer tissue has not been fully elucidated. Methods: Seprase expression and distribution in gastric cancer specimens obtained from 133 patients were examined by immunohistochemistry and immunoblotting. Results: Immunohistochemistry showed that in intestinal-type cancer, which includes well and moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 15 publications
3
40
1
Order By: Relevance
“…Furthermore, this process degrades local extracellular matrix components that are required for cell migration and matrix invasion during tumor invasion, angiogenesis and metastasis (21). Previous studies have revealed that seprase overexpression was evident in stromal fibroblasts and tumor cells in invasive breast, gastric, colonic and cervical carcinomas; however, it was absent or undetectable in all normal tissue cells, with the exception of cells involved in the early stages of wound healing (22)(23)(24)(25). In addition, an in vivo study using a mouse model of human breast cancer, demonstrated that seprase increased microvessel density and promoted rapid tumor growth (26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this process degrades local extracellular matrix components that are required for cell migration and matrix invasion during tumor invasion, angiogenesis and metastasis (21). Previous studies have revealed that seprase overexpression was evident in stromal fibroblasts and tumor cells in invasive breast, gastric, colonic and cervical carcinomas; however, it was absent or undetectable in all normal tissue cells, with the exception of cells involved in the early stages of wound healing (22)(23)(24)(25). In addition, an in vivo study using a mouse model of human breast cancer, demonstrated that seprase increased microvessel density and promoted rapid tumor growth (26).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated 27 cases of infiltrating ductal carcinoma of the breast and found that the carcinoma cells as well as the stromal cells express seprase (2). The finding of carcinoma cell expression of seprase is supported by the constitutive expression of seprase in several human breast cancer cell lines and by its expression in the malignant cells of a number of other carcinomas including melanoma and gastric cancer (11,14,30). On the other hand, two other studies of human breast cancer, including one survey of 112 cases, have indicated that seprase is detected primarily in the reactive stromal fibroblasts, suggesting that reactive fibroblasts are the main source of seprase in breast cancer (21,29).…”
Section: Seprase Promotes Growth Of Breast Cancer Cellsmentioning
confidence: 96%
“…Similar pattern of expression has been reported in esophageal adenocarcinoma where FAP expression was observed in >98% of the cases in epithelial carcinoma cells. 62 FAP has also been reported to be overexpressed in epithelial as well as adjacent stromal cells in other cancers including diffuse-type of gastric cancer, 63 colorectal cancer 64 and gastric carcinoma. 65 …”
Section: Genes Overexpressed In Esccmentioning
confidence: 99%